Horseshoe kidney with high bifurcation of abdominal aorta: a rare imaging finding - Pal, Rajeev Kumar; Tepale, Rakhee V. (International Journal of Research in Medical Sciences, 2021)
Vascular variations of the bifurcation of the abdominal aorta (BAA) are rare, and they are usually discovered incidentally. We report a unique clinically and surgically significant case of variations of the abdominal aorta as related to the location and type of bifurcation. A high-positioned bifurcation of the abdominal aorta upon a horseshoe kidney at the level of upper L2 vertebral body was detected during contrast-enhanced abdominal computed tomography scan. Due to the halted ascent in horseshoe kidney, abdominal vascular anomalies are common: usually, multiple renal arteries arise from the distal aorta or iliac arteries; this is important when these patients undergo any procedure, particularly abdominal angiogram. The awareness of the variations of the abdominal aorta is of great importance during surgery and interventional radiological procedures to reduce complications during abdominal and spinal interventions, as well as for radiologists for precise interpretation of angiograms.